A biotroph sets the stage for a necrotroph to play: ‘Candidatus Phytoplasma solani’ infection of sugar beet facilitated Macrophomina phaseolina root rot - Duduk, Nataša; Vico, Ivana; Kosovac, Andrea; Stepanović, Jelena; Ćurčić, Živko; Vučković, Nina; Rekanović, Emil; Duduk, Bojan (Frontiers in Microbiology, 2023)
'Candidatus Phytoplasma solani' (stolbur phytoplasma) is associated with rubbery taproot disease (RTD) of sugar beet (Beta vulgaris L.), whereas Macrophomina phaseolina is considered the most significant root rot pathogen of this plant in Serbia. The high prevalence of M. phaseolina root rot reported on sugar beets in Serbia, unmatched elsewhere in the world, coupled with the notorious tendency of RTD-affected sugar beets to rot, has prompted research into the relationship between the two diseases. This study investigates the correlation between the occurrence of RTD of sugar beet and the presence of root rot fungal pathogens in a semi-field 'Ca. P. solani' transmission experiment with cixiid vector Reptalus quinquecostatus, as well as in naturally infected sugar beets in open fields. Our results showed that: i) R. quinquecostatus transmitted 'Ca. P. solani' to sugar beets which induced typical RTD root symptoms; ii) M. phaseolina root rot was present exclusively in 'Ca. P. solani' infected sugar beets in both the semi-field experiment and naturally infected sugar beets; and that iii) even under favorable environmental conditions for the pathogen, M. phaseolina did not infect sugar beets, unless the plants had been infected previously with phytoplasma.